Identification of Somatic Mutations in CLCN2 in Aldosterone-Producing Adenomas - Rege, Juilee (J Endocr Soc, 2020)
Somatic mutations driving aldosterone production have been identified in approximately 90% of aldosterone-producing adenomas (APAs) using an aldosterone synthase (CYP11B2) immunohistochemistry (IHC)-guided DNA sequencing approach. In the present study, using CYP11B2-guided whole-exome sequencing (WES) and targeted amplicon sequencing, we detected 2 somatic variants in CLCN2 in 2 APAs that were negative for currently known aldosterone-driver mutations. The CLCN2 gene encodes the voltage-gated chloride channel ClC-2. CLCN2 germline variants have previously been shown to cause familial hyperaldosteronism type II. Somatic mutations in CLCN2 were identified in 2 of 115 APAs, resulting in a prevalence of 1.74%. One of the CLCN2 somatic mutations (c.G71A,p.G24D) was identical to a previously described germline variant causing early-onset PA, but was present only as a somatic mutation. The second CLCN2 mutation, which affects the same region of the gene, has not been reported previously (c.64-2_74del). These findings prove that WES of CYP11B2-guided mutation-negative APAs can help determine rarer genetic causes of sporadic PA.